Negative electrodes for supercapacitors with good performance using conductive bismuth-catecholate metal–organic frameworks. Issue 15 (20th March 2023) - Chen, Si; Zhang, Haoliang; Li, Xu; Liu, Yong; Zhang, Mingyi; Gao, Xiangyang; Chang, Xin; Pu, Xiangjun; He, Chunqing
Abstract : The Bi(HHTP) nanobelt electrode with charge storage mechanisms for battery-type and surface-capacitive modes displayed a high specific capacitance of 234.0 F g −1 . Abstract : Metal–organic frameworks (MOFs) have attracted increasing research interest in various fields. Unfortunately, the poor conductivity of most traditional MOFs considerably hinders their application in energy storage. Benefiting from the full charge delocalization in the atomic plane, two-dimensional conductive coordination frameworks achieve good electrochemical performance. In this work, π–π coupling conductive bismuth-catecholate nanobelts with tunable lengths, Bi(HHTP) (HHTP = 2, 3, 6, 7, 10, 11-hexahydroxytriphenylene), are synthesized by a simple hydrothermal reaction and their length-dependent electrochemical properties are also investigated. The Bi(HHTP) nanobelts (about 10 μm in length) possess appropriate porosity, numerous redox active sites and good electrical conductivity. Being a negative electrode for supercapacitors, Bi(HHTP) nanobelts display a high specific capacitance of 234.0 F g −1 and good cycling stability of 72% after 1000 cycles. Furthermore, the mechanism of charge storage is interpreted for both battery-type and surface-capacitive behavior. It is believed that the results of this work will help to develop battery-type negative electrode materials with promising electrochemical performance using some newly designed π–π coupling conductive coordination frameworks.